1997
DOI: 10.1017/s0950268897008236
|View full text |Cite
|
Sign up to set email alerts
|

Present characteristics of symptomatic amebiasis due to Entamoeba histolytica in the east-southeast area of Tokyo

Abstract: Admitted medical records, from January 1988 to December 1995, of 28 symptomatic amebic patients who lived in the east-southeast area of Tokyo were studied retrospectively, in order to find the present characteristics of symptomatic amebiasis due to Entamoeba histolytica in this area. Categorized by disease, there were 14 cases of colitis, 9 cases of liver abscess, 4 cases of colitis with liver abscess, and 1 case of liver abscess with brain abscess. Patients consisted of 26 Japanese males, 0 Japanese females, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 11 publications
6
15
0
2
Order By: Relevance
“…In the present study, the iron score in the three nonALAcontrol females was 1, 0, and 0, respectively, as compared to a score of 5 in the lone female patient of ALA.This low iron, which is unsuitable for the growth of E. histolytica, might act as a protective factor against the invasion of E. histolytica in such females. This negative predilection of ALAfor females correlates well with previous reports that concur with the low incidence of ALAin young females (9,(17)(18)(19)(20). Other low iron states like pregnancy, infancy, young adolescence and elderly age group (24) and the low incidence of ALAseen in these groups in various studies (9,(17)(18)(19)(20)25) further lends support to the protective role of low iron in ALA. Iron stores in the body are normally maintained in the liver (26).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the iron score in the three nonALAcontrol females was 1, 0, and 0, respectively, as compared to a score of 5 in the lone female patient of ALA.This low iron, which is unsuitable for the growth of E. histolytica, might act as a protective factor against the invasion of E. histolytica in such females. This negative predilection of ALAfor females correlates well with previous reports that concur with the low incidence of ALAin young females (9,(17)(18)(19)(20). Other low iron states like pregnancy, infancy, young adolescence and elderly age group (24) and the low incidence of ALAseen in these groups in various studies (9,(17)(18)(19)(20)25) further lends support to the protective role of low iron in ALA. Iron stores in the body are normally maintained in the liver (26).…”
Section: Discussionsupporting
confidence: 91%
“…This negative predilection of ALAfor females correlates well with previous reports that concur with the low incidence of ALAin young females (9,(17)(18)(19)(20). Other low iron states like pregnancy, infancy, young adolescence and elderly age group (24) and the low incidence of ALAseen in these groups in various studies (9,(17)(18)(19)(20)25) further lends support to the protective role of low iron in ALA. Iron stores in the body are normally maintained in the liver (26). In a study by Bothwell et al (27) in 1984, hepatic iron levels amongBlack subjects with amoebiasis were studied.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous reports have shown many invasive amebiasis in Japanese homosexual men (10)(11)(12). These results indicate that E. hystolytica is not always detected as non-pathogenic colonization and homosexual behavior is one of the risk factors of amebiasis in Japan.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, in Turkey and in Japan, males were found more affected than females (Ohnishi and Murata, 1997;Ozyurt et al, 2007). On the other hand, other studies conducted in Turkey (Ozgumus and Efe, 2007) and in Pakistan (Ejaz et al, 2011) showed a prevalent and significant female infection.…”
Section: Period Of Communicabilitymentioning
confidence: 99%